Volcanoes of Auckland - Hayward, Bruce W. (Auckland University Press, 2019)
A fully illustrated field guide for Aucklanders and visitors to take with them out among the 53 volcanoes that shape this city. Volcanoes of Auckland is a handy field guide to the fiery natural world that so deeply shapes New Zealand's largest city - from Rangitoto to One Tree Hill, Lake Pupuke to Ōrākei Basin. For tens of thousands of years, volcanoes have profoundly shaped the area's geology and geography. And for hundreds of years, volcanoes have played a key part in the lives of Māori and Pākehā - as sites for pā, kūmara gardens or twentieth-century military fortifications, as sources of stone and water, and now as parks and reserves for all to enjoy. In a new format designed for the backpack (and including three newly recognised craters), the field guide features: an accessible introduction to the science of eruptions, including dating and the next eruption a history of Māori and Pākehā uses of the volcanoes an illustrated guide to each of Auckland's 53 volcanoes, including where to go and what to do aerial photography, maps and historic photographs - over 400 illustrations, 80% of them new. This field guide will help readers engage afresh with the history, geography and geology of Auckland's unique volcanic landscape. How many volcanoes are there? When did they erupt and how do we know? Will there be another eruption in Auckland and, if so, where and when? Will we have sufficient warning to evacuate in time? What is a lava cave, a volcanic bomb or a tuff ring? Why were Auckland's volcanoes such an attraction to early Māori? Why is it that Auckland's freshest water comes out of our volcanoes? This book answers these and many more questions."-- Publisher's description.